Effect of thermal cycling and aging stages on the microstructure and bending strength of a selective laser melted 300-grade maraging steel - Conde, F. F.; Escobar, J. D.; Oliveira, J. P.; Béreš, M.; Jardini, A. L.; Bose, W. W.; Avila, J. A. [UNESP] (Elsevier, 2019)
Additive manufacturing techniques allow the creation of complex parts in a layer by layer fashion, bringing new opportunities in terms of applications and properties when compared to conventional manufacturing processes. Among other ultra-high-strength steels, the 18 Ni maraging 300 steel offers a good toughness/strength ratio. However, when fabricated by additive manufacturing, this steel presents lower ductility and strain-hardening than its forging counterparts. One way to enhance ductility and toughness is to promote martensite-to-austenite reversion. Therefore, in the present study, 18 Ni maraging steel powder was processed by selective laser melting and different heat treatments were applied to the built parts, aiming for homogenization, microstructural refinement and martensite-to-austenite reversion. Thermodynamic simulations were used to assess a range of temperatures for the reversion heat treatments. Microstructural characterization was performed by scanning electron microscopy, electron backscattered diffraction and x-ray diffraction.
Keywords: 18 Ni; Additive manufacturing selective laser melting ductility; Maraging 300